A possible association between a dysfunctional skin barrier (filaggrin null-mutation status) and diabetes: a cross-sectional study. Issue 1 (15th March 2011) - Thyssen, Jacob P; Linneberg, Allan; Carlsen, Berit C; Johansen, Jeanne D; Engkilde, Kåre; Hansen, Torben; Pociot, Flemming; Pedersen, Oluf; Meldgaard, Michael; Szecsi, Pal B; Stender, Steen; Menné, Torkil
Abstract : Background: Filaggrin proteins are located in the skin and prevent epidermal water loss and impede the entry of micro-organisms, allergens and chemicals. Filaggrin null mutations are strongly associated with ichthyosis vulgaris and atopic dermatitis. Objective: The authors aimed to investigate the association between filaggrin null mutations, atopic dermatitis and diabetes. Design: A random sample of 3335 adults from the general population in Denmark was filaggrin-genotyped for R501X and 2282del4 null-mutations and questioned about atopic dermatitis and diabetes. Furthermore, two independent study populations of patients with type 1 (n=104) or 2 (n=774) diabetes were genotyped. Results: In a crude data analysis, a positive association was detected between the filaggrin null genotype and, respectively, subjects from the general population who reported diabetes (p=0.04) and patients with established type 2 diabetes (p=0.073). Adjustment for age and gender resulted in significant associations for patients with type 2 diabetes (p=0.048) and subjects with self-reported diabetes (p=0.032). Conclusions: Adult Danes with a filaggrin null genotype had a significantly increased prevalence of self-reported diabetes. This finding was replicated when an independent sample of Danish patients with established type 2 diabetes was compared with control subjects from the general population.